The Current Status and Work of Three Rs Centres and Platforms in Europe*. Issue 6 (November 2022) - Neuhaus, Winfried; Reininger-Gutmann, Birgit; Rinner, Beate; Plasenzotti, Roberto; Wilflingseder, Doris; De Kock, Joery; Vanhaecke, Tamara; Rogiers, Vera; Jírová, Dagmar; Kejlová, Kristina; Knudsen, Lisbeth E.; Nielsen, Rasmus Normann; et al.
The adoption of Directive 2010/63/EU on the protection of animals used for scientific purposes has given a major push to the formation of Three Rs initiatives in the form of centres and platforms. These centres and platforms are dedicated to the so-called Three Rs, which are the Replacement, Reduction and Refinement of animal use in experiments. ATLA 's 50th Anniversary year has seen the publication of two articles on European Three Rs centres and platforms. The first of these was about the progressive rise in their numbers and about their founding history; this second part focuses on their current status and activities. This article takes a closer look at their financial and organisational structures, describes their Three Rs focus and core activities (dissemination, education, implementation, scientific quality/translatability, ethics), and presents their areas of responsibility and projects in detail. This overview of the work and diverse structures of the Three Rs centres and platforms is not only intended to bring them closer to the reader, but also to provide role models and show examples of how such Three Rs centres and platforms could be made sustainable. The Three Rs centres and platforms are very important focal points and play an immense role as facilitators of Directive 2010/63/EU 'on the ground' in their respective countries. They are also invaluable for the wide dissemination of information and for promoting the implementation of the Three Rs in general.